Lipocalin-2 enhances angiogenesis in rat brain endothelial cells via reactive oxygen species and iron-dependent mechanisms - Wu, Limin (J Neurochem, 2015)
Inflammation is a key part of central nervous system pathophysiology. However, inflammatory factors are now thought to have both beneficial and deleterious effects. Here, we examine the hypothesis that lipocalin-2, an inflammatory molecule that can be upregulated in the distressed central nervous system, may enhance angiogenesis in brain endothelial cells. Adding lipocalin-2 (0.5–2.0µg/ml) to RBE.4 rat brain endothelial cells significantly increased matrigel tube formation and scratch migration, and also elevated levels of iron and reactive oxygen species (ROS). Co-treatment with a radical scavenger (UE83836E), a Nox inhibitor (apocynin) and an iron chelating agent (deferiprone) significantly dampened the ability of lipocalin-2 to enhance tube formation and scratch migration in brain endothelial cells. These findings provide in vitro proof of the concept that lipocalin-2 can promote angiogenesis via iron- and ROS-related pathways, and support the idea that lipocalin-2 may contribute to the neurovascular recovery aspects of inflammation.